Using Sustainable Materials in the Design of Sports Halls in Order to Improve the Quality of Sports Spaces - Hassani, Hussein; Golizadeh, Reza (Journal of History Culture and Art Research, 2017)
Abstract The establishment of any urban element in the location of the city follows certain rules and principles that in the case of observing the success and efficiency of that element will result in that specific location. Therefore, this study has been conducted with the aim to find out the most proper place among sports complexes in Urmia to redesign. In this regard, requirements and obligations of location finding were identified after studying international experiences and study the top regulations and documents, then, effective parameters were categorized in the two levels of main indices and options according to AHP. In following, information received from opinions of experts, managers and professionals were determined in determine the importance of the indexes and analysis and weights of indexes. Finally, Urmia two thousand seater sports hall was selected among other candidate places as the best place to redesign and also environmental problems are considered as an important situation in construction. Waste Management has activated the warning signs and alerts to the environment. Reuse, recycle and reduce the wastes is the only ways to recycle created wastes. However, these executive cases have more space for progress. In this study, we investigate the use of building materials in two-thousand seater sports hall of Young house of Urmia that emphasis is on the recyclable materials. Recycling as one of the strategies is to minimize wastes. And ultimately Sport Cultural of Young house has been redesigned from sustainable materials and suggestion was designed and presented with more details ranging from architectural maps and sections and the main structure of the stadium in three-dimensional.